An interpretable transformer based approach to classify Malaria from blood cell images - Islam, Mehafuza; Al Mamun, S.M. Abdulla (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.